Análisis, diseño, construcción e implementación de un sistema web para la toma de decisiones de la "Unidad de Planificación y Estadística Distrital" mediante el uso de herramientas libres para la Dirección Distrital de Salud 17D04. - Cruz Flores, Néstor Paul (2017)
The project aims to analyze, design, build and implement a WEB system that facilitates decision making in the "Planning and Statistics Unit" using free tools for the District Health Directorate 17D04 "PUENGASI A ITCHIMBIA". For the management of the project was used the SCRUM methodology, for the construction of the system was used open source tools: Liferay for content management, PostgreSQL for database management and Birt for the construction and visualization of reports. As result final, a decision-making system was obtained, based on the indicators generated in the reports that were implemented in the web application, in a faster and more efficient way using friendly and easy-to-understand interfaces, fulfilling and satisfying with the needs of the Unit Area of Planning and District Statistics.